Integrating fraud hexagon into fraud control system: a study of Indonesia - Kuntadi, Cris (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The fraud control system is an assessment of the risk of irregularities which is a proactive process that aims to identify and overcome organizational vulnerabilities due to conditions carried out by internal and external parties to the organization. The purpose of this research is to determine the effectiveness of the newly formed Fraud Control System regulations with the integration of Fraud Hexagon to formulate effective fraud prevention and detection procedures. This study is based on empirical literature collected and interpreted from the Fraud Control System and Fraud Hexagon to formulate effective fraud prevention and detection procedures at BPKP and KemenPAN RB. The result is that BPKP and KemenPAN RB must start a joint assessment rather than working separately, because the two anti-fraud frameworks complement each other, so they must be assessed coherently to allow for a check and balance mechanism. BPKP and KemenPAN RB must also design a fraud prevention and detection framework at the national level so that the assessment also includes top level leadership. It is hoped that the implications of the research can help Indonesia to perfect a more holistic fraud control mechanism so that the effectiveness of the Fraud Control System is even better.